2001
DOI: 10.1053/jlts.2001.0070157
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of Epstein-Barr viral load in solid-organ transplantation

Abstract: Epstein‐Barr virus (EBV) DNA was quantitated in peripheral blood mononuclear cells (PBMC) from 25 healthy subjects, 105 asymptomatic solid‐organ transplant (SOT) recipients, and 15 SOT recipients with symptomatic EBV infections by using a newly developed quantitative‐PCR technique. Patients with symptomatic EBV infections had significantly higher (P < 0.001) median EBV DNA levels than asymptomatic SOT recipients and immunocompetent individuals. In SOT recipients, the positive predictive value of EBV DNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Before the occurrence of symptomatic disease there is a period of approximately 2 to 6 weeks when the rising EBV load can be detected by PCR. PTLD is associated with a very high EBV load circulating in the peripheral blood: Ͼ1,000 copies of EBV genomes/10 5 PBLs in most cases and greater than 200 copies/10 5 PBLs with rare exceptions (4,11,12,19,21,23,29,34,36,38,39,46). Resolution of EBV infection in pediatric solid-organ transplant recipients is often accompanied by a persistent high circulating EBV load 2 to 3 orders of magnitude higher than the viral load observed in latently infected immunocompetent individuals.…”
Section: Peripheral Blood Lymphocytes) Fish Analysis Revealed That Tmentioning
confidence: 99%
“…Before the occurrence of symptomatic disease there is a period of approximately 2 to 6 weeks when the rising EBV load can be detected by PCR. PTLD is associated with a very high EBV load circulating in the peripheral blood: Ͼ1,000 copies of EBV genomes/10 5 PBLs in most cases and greater than 200 copies/10 5 PBLs with rare exceptions (4,11,12,19,21,23,29,34,36,38,39,46). Resolution of EBV infection in pediatric solid-organ transplant recipients is often accompanied by a persistent high circulating EBV load 2 to 3 orders of magnitude higher than the viral load observed in latently infected immunocompetent individuals.…”
Section: Peripheral Blood Lymphocytes) Fish Analysis Revealed That Tmentioning
confidence: 99%
“…A high load of EBV in the peripheral blood (>1000 copies/10 5 PBMCs) is strongly associated with a diagnosis of PTLD (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). This load is at least 2-3 orders of magnitude greater than the viral load measured in normal individuals, and is detected 2-6 wk before patients present with symptoms of PTLD (16,20).…”
mentioning
confidence: 99%
“…Estimates of the incidence of disease range from 0.7% (19) to 32% (7) in various allograft recipients, depending on a number of factors. From a large number of separate studies, it has been shown that the diagnosis of PTLD is also associated with a very high EBV load in the peripheral blood (Ͼ1,000 copies/10 5 peripheral blood mononuclear cells [PBMCs]) (5,6,8,9,10,15,17,18,23,26,29,31,32,35). While healthy immunocompetent adults harbor an average of approximately 0.01 to 0.1 genomes per 10 5 PBMCs (29), PTLD patients typically have viral loads several orders of magnitude greater at the time of diagnosis.…”
mentioning
confidence: 99%